Elemental Mobility and Provenance in Sediments: A Geochemical Study of Deccan Basalts, Bay of Bengal, and Northern China - Yelwa Jibrin (International Journal of Minerals, 2024)
Twenty-eight sediment samples from seventeen rivers, including the Krishna headwaters and the west-flowing Western Ghat rivers, draining the Deccan Trap basalts, were analyzed for major elements (Na, Ca, Mg, K, Al, Ti, Fe) and trace elements (Sr, Ba, Mn, P, V, Cr, Ni, Cu, and Zn). The mobility of these elements, especially Na, Ca, Mg, and Sr, was assessed by comparing their abundances in sediments and dissolved phases. Approximately 60% less Na, Ca, Mg, and Sr is present in the sediments compared to the parent basalts, indicating simultaneous release during chemical weathering. K and Ba showed limited mobility, with strong correlations suggesting association in rock-forming minerals. Because secondary minerals are formed during weathering, the sediments are richer in Al, Fe, and Ti. The study also highlights how Fe and Al fractionate during weathering and erosion, with Fe-Ti associations suggesting their resistance to weathering or scavenging by Fe oxy-hydroxides. Minor elements (Mn, P, V, Cr, Ni, Cu, and Zn) show considerable variability in abundance, with zinc potentially influenced by anthropogenic sources. In comparison, major and trace elements from 110 surface sediment samples from the mid-Bay of Bengal were analyzed, indicating intermediate weathering with a Chemical Index of Alteration (CIA) averaging 72.07. Provenance analysis revealed that the sediments primarily originate from Himalayan and Indian sources, with estimated contributions of 83.5% and 16.5%, respectively. Elemental distribution patterns suggest that surface circulation and turbidity currents transport Indian and Himalayan materials across the Bay. Lastly, rare earth element (REE) analyses from a northern China grassland transect revealed variations in REE distributions along an aridity gradient. The study examines the factors influencing REE mobility and fractionation, including climatic and edaphic conditions, to understand how long-range climatic variations affect elemental redistribution in soils.
Keywords: Aridity gradient; Bay of Bengal; Deccan basalts; chemical weathering; geochemistry; major elements; northern China transect; rare earth elements (REE); sediment provenance; trace elements